Head nurses’ transformational leadership and nurses’ job engagement: the mediating role of horizontal violence among nurses - Liu, Xu Yan; Liang, Ren Long; Li, Yi Wei; Yuan, Yin; Ruan, Tingting (Frontiers in Public Health, 2025)
BackgroundHorizontal violence among nurses is relatively prevalent and may affect nurses’ level of job engagement. By integrating Affective Events Theory (AET) and Conservation of Resources Theory (COR), This study aims to verify the mediating effect of horizontal violence among nurses on the relationship between head nurses’ transformational leadership style and nurses’ job engagement. It is expected to provide a new perspective for the innovation of theoretical application in the field of nursing management.MethodsThis study adopted a cross-sectional design, A total of 317 nurses from five tertiary grade A general hospitals in Southwest China. Data were collected through a general information questionnaire, a transformational leadership questionnaire, a simplified version of the Utrecht Work Engagement Scale, and an inter-nurse horizontal violence questionnaire. SPSS 26.0 was used for correlation analysis, and Amos 26.0 for constructing the structural equation model, and the Bootstrap method for testing the mediating effect.ResultsThe results indicated that horizontal violence among nurses partially mediated the relationship between head nurses’ transformational leadership style and nurses’ job engagement. Specifically, head nurses’ transformational leadership style could not only directly improve nurses’ job engagement but also indirectly enhance it by reducing horizontal violence. Horizontal violence among nurses plays a partial mediating role in the relationship between head nurses’ transformational leadership style and nurses’ job engagement.ConclusionNursing managers should focus on cultivating and selecting head nurses with a transformational leadership style, and implement interventions from two dimensions: regulating affective events and interrupting resource depletion. For instance, by recognizing contributions, supporting innovation, providing care and support, making fair decisions, and establishing effective communication mechanisms, a positive organizational culture can be fostered. This will thereby reduce horizontal violence among nurses and improve their job engagement.